State-Level Changes in Energy Intensity and Their National Implications - Bernstein, Mark A. (RAND Corporation, 2003)
The 2001 National Energy Policy calls for continued reductions in energy intensity (energy consumption per dollar of gross economic output). This study was part of an effort to identify state-level factors that may contribute to efficient energy use nationwide. The authors examined changes in energy intensity in 48 states and in the states' energy-consuming sectors from 1977 through 1999. Some factors that may explain differences in states' energy intensity are energy prices, new construction, capacity utilization, population, climate, tech innovations, and government energy policies.